Role of exosomes in diagnosis, prognostication, and treatment of pediatric solid tumors - Shaikh M. Ghufran; Morgan L. Brown; Elizabeth A. Beierle (Molecular Therapy: Oncology)
Cancer is the second leading cause of death in children, and solid tumors make up 30% of childhood cancers. Molecular profiling of pediatric solid tumors allows a personalized approach to therapy, but this approach mostly relies on surgical biopsy, which is invasive and carries the risk of complications. Liquid biopsy serves as a reliable alternative and a minimally invasive tool for diagnosing, prognosticating, and residual disease monitoring in childhood cancers. This review outlines the potential of exosomes as informative liquid biopsies in pediatric solid tumors. Studies highlighting the potential applications and clinical utility of exosomes and their molecular constituents as prognosticators and therapies in common childhood solid tumors, including neuroblastoma, medulloblastoma, sarcoma, and hepatoblastoma, have been overviewed. We also discuss the limitations and technical challenges of utilizing exosomes for pediatric solid tumors.